UPAYA GURU AKIDAH AKHLAK DALAM MENGENALKAN SELF HEALING MELALUI MIND HEALING THERAPY PADA PESERTA DIDIK KELAS XI IPA 5 DI SMA ANNUR BULUAWANG - Zakia Bahama Putri Hawa; Dian Mohammad Hakim; Adi Sudrajat (VICRATINA, 2022)
The efforts of the moral aqidah teacher in the introduction and appreciation of and creating an exemplary atmosphere and habituation in practicing commendable morals and Islamic etiquette through providing examples of behavior and how to practice them in daily life, as well as provision for the next level of education. SMA ANNUR Bululawang is an educational institution based in Islamic boarding schools and each graduate is considered to be good at religion and becomes a moral figure in society. In this case, the efforts of the moral aqidah teacher become the most important role in learning and providing examples of good behavior so that it can be a provision for students. Researchers used the method of observation, interviews, and documentation involving homeroom teachers, teachers of morals and students. Students experience an increase in 1) improving good relations with God and humans 2) increasing worship 3) becoming a trusting servant 4) believing that Allah is the best regulator 5) perseverance in studying.